2019
DOI: 10.1002/jcb.28391
|View full text |Cite
|
Sign up to set email alerts
|

Bowman‐Birk inhibitor modifies transcription of autophagy and apoptosis genes in an in vitro model of Alzheimer's disorder

Abstract: Alzheimer, a current neurodegenerative disorder has adverse effects on memory and behavior. β-Amyloid peptide accumulations are the hallmarks of Alzheimer. Dysfunction of autophagy and apoptosis is detected in Alzheimer's disease. The effect of Bowman-Birk inhibitor (BBI), purified from soybean, was investigated in autophagy and apoptosis in Alzheimer treatment. Treated-PC12 cells with 1000 nM HgCl 2 induced amyloid β (Aβ) accumulation. Treatment of PC12 cells with 1000 nM HgCl 2 and then 500 μg/mL BBI could d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It has been suggested that soybean BBI could be effective in the inhibition of Alzheimer's disease. Akbari et al [205] studied the effect of BBI on in vitro model of Alzheimer's disorder in which accumulation of amyloid β (Aβ) in PC12 cells was stimulated with HgCl 2 . It was shown that BBI inhibited the accumulation of Aβ by inducing autophagy and decreased apoptosis, which is regarded as a key event in neurodegenerative diseases.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…It has been suggested that soybean BBI could be effective in the inhibition of Alzheimer's disease. Akbari et al [205] studied the effect of BBI on in vitro model of Alzheimer's disorder in which accumulation of amyloid β (Aβ) in PC12 cells was stimulated with HgCl 2 . It was shown that BBI inhibited the accumulation of Aβ by inducing autophagy and decreased apoptosis, which is regarded as a key event in neurodegenerative diseases.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…BBIC has been reported to prevent the initiation of tumors and cause cell death in in vivo and invitro cancer models (Kennedy, 1998;Kennedy and Wan, 2002). Besides its chemo-preventive and anti-inflammatory properties (Clemente et al,2011), BBI has been recently reported to be effective in the treatment of Alzheimer's disease (Akbari et al, 2019) and inhibition of HIV replication in macrophages (Ma et al, 2016). Further, in the backdrop of the fact that SARS-CoV-2, the causative agent of COVID-19 pandemic, requires the expression of self-encoded chymotrypsin-like protease for its replication in the host cell (Cascella et al, 2020), BBI in soybean may show an inhibitory effect on the multiplication of this novel virus in human cell due to its chymotrypsin inhibiting property.…”
Section: Academicpresmentioning
confidence: 99%
“…9,10 BBIs have been studied extensively due to their therapeutic potential, against certain types of cancer, 11 Alzheimer's disease, 12 autoimmune disease, fungal infections, and inflammatory disorders. 13,14 As the pathogenesis of pancreatitis is associated with the hydrolyzing enzymes, therefore, the BBIs may play their role in the management of pancreatitis by inhibiting such enzymes. Both KTIs and BBIs are present in a wide variety of plants, however, Bowman-Birk-type protease inhibitors have been mostly reported from the legume family of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, the Bowman–Birk‐type of protease inhibitors are relatively large proteins as compared to Kunitz type‐inhibitors, with several disulfide bonds 9,10 . BBIs have been studied extensively due to their therapeutic potential, against certain types of cancer, 11 Alzheimer's disease, 12 autoimmune disease, fungal infections, and inflammatory disorders 13,14 . As the pathogenesis of pancreatitis is associated with the hydrolyzing enzymes, therefore, the BBIs may play their role in the management of pancreatitis by inhibiting such enzymes.…”
Section: Introductionmentioning
confidence: 99%